Graptopetalum trujilloi (Crassulaceae), a new haplostemonous and critically endangered species endemic to western Mexico: comments on taxa of subg. Glassia - Vázquez-García, J. Antonio; Rosales-Martínez, C. Santiago; Acevedo-Rosas, Raúl (Phytotaxa, 2022)
Graptopetalum trujilloi (subg. Glassia, Crassulaceae), a new haplostemonous species from San Gabriel municipality, Jalisco, Mexico is described and illustrated. Its morphologically closest species is G. rosanevadoense. It differs from the latter in having a smaller habit, more numerous primary branches per inflorescence, larger mean flower density per 10 cm of the scape, fewer flowers per basal branch, smaller flower diameter, petals greenish with transversal inconspicuous red stripes, narrower petals, filaments greenish to distally reddish and carpels abaxially obtuse. A key to the haplostemonous species of Graptopetalum is provided and, according to IUCN criteria, the species was assessed as critically endangered (CR).